Label-free detection of glycoproteins by the lectin biosensor down to attomolar level using gold nanoparticles - Bertok, Tomas (Talanta, 2013)
We present here an ultrasensitive electrochemical biosensor based on a lectin biorecognition capable to detect concentrations of glycoproteins down to attomolar (aM) level by investigation of changes in the charge transfer resistance (R(ct)) using electrochemical impedance spectroscopy (EIS). On polycrystalline gold modified by an aminoalkanethiol linker layer, gold nanoparticles were attached. A Sambucus nigra agglutinin was covalently immobilised on a mixed self-assembled monolayer formed on gold nanoparticles and finally, the biosensor surface was blocked by poly(vinylalcohol). The lectin biosensor was applied for detection of sialic acid containing glycoproteins fetuin and asialofetuin. Building of a biosensing interface was carefully characterised by a broad range of techniques such as electrochemistry, EIS, atomic force microscopy, scanning electron microscopy and surface plasmon resonance with the best performance of the biosensor achieved by application of HS-(CH(2))(11)-NH(2) linker and gold nanoparticles with a diameter of 20 nm. The lectin biosensor responded to an addition of fetuin (8.7% of sialic acid) with sensitivity of (338 ± 11) Ω decade(-1) and to asialofetuin (≤ 0.5% of sialic acid) with sensitivity of (109 ± 10) Ω decade(-1) with a blank experiment with oxidised asialofetuin (without recognisable sialic acid) revealing sensitivity of detection of (79 ± 13) Ω decade(-1). These results suggest the lectin biosensor responded to changes in the glycan amount in a quantitative way with a successful validation by a lectin microarray. Such a biosensor device has a great potential to be employed in early biomedical diagnostics of diseases such as arthritis or cancer, which are connected to aberrant glycosylation of protein biomarkers in biological fluids.